Dinamika Pembentukan Undang-Undang Di Indonesia: Antara Kepentingan Politik Dan Kebutuhan Hukum - Gokma Toni Parlindungan S (Journal of Global Legal Review, 2025)
This article examines the dynamics of lawmaking in Indonesia by highlighting the tension between political interests and the legal needs of society. Through a juridical-normative approach and case study analysis, this study finds that the legislative process is still dominated by political elites and often ignores the principle of meaningful public participation. Information technology innovation through participatory digital channels has not been effective in boosting substantive citizen involvement due to weak infrastructure, digital literacy, and minimal institutional commitment. This imbalance between political interests and public aspirations has a direct impact on declining legal legitimacy, increasing social resistance, and low public trust in legislative institutions. This study recommends reforming the legislative system based on transparency, accountability, and protection of citizens' participatory rights as a strategic step to strengthen the quality of law and democracy in Indonesia.